Electrospun TiO2–SiO2 fibres with hierarchical pores from phase separation. Issue 19 (28th April 2017) - Wang, Yun; Huang, Haibo; Li, Guannan; Zhao, Xiaojuan; Yu, Lin; Zou, Chen; Xu, Yan
Abstract : We provide a general phase separation strategy for the fabrication of TiO2 –SiO2 fibres with hierarchical meso-/macropores via a typical electrospinning procedure. Abstract : Design and fabrication of hierarchically porous inorganic fibres holds exciting implications for applications in catalysis, separation, and energy devices. In this article, we present a general phase separation strategy for the fabrication of TiO2 –SiO2 fibres with hierarchical pores via a typical electrospinning procedure. The porous hierarchy of the as-fabricated products and the possible formation mechanism have been investigated in detail. The results confirmed that the hydrophilic–hydrophobic repulsion between the PVP@TBT@TEOS 3D network complex and the solvent, the hydrolysis and polycondensation of inorganic alkoxides, and the slow solvent evaporation during the process of electrospinning may be responsible for the phase separation, leading to the formation of macropores in the fibres. The obtained hierarchically macro-/mesoporous TiO2 –SiO2 fibres exhibited amazing structure stability even at a high calcination temperature of 850 °C. The current work may guide the further design of functional inorganic fibres with controllable hierarchical porous structures.